A multicenter retrospective investigation on the efficacy of perioperative oral management in cancer patients. Issue 10 (March 2020) - Yamada, Shin-Ichi; Soutome, Sakiko; Hasegawa, Takumi; Tojyo, Itaru; Nakahara, Hirokazu; Kawakami, Mao; Hirose, Marina; Fujita, Shigeyuki; Komori, Takahide; Kirita, Tadaaki; Shibuya, Yasuyuki; Umeda, Masahiro; et al.
Abstract : Abstract: Patients develop a number of oral complications during cancer treatments. Oral bacteria are associated with the onset of dental focal infections and the progression of oral mucositis. Dental focal infections are frequently associated with the systemic onset of bacteremia, sepsis, and pneumonia. The degeneration of oral function with these complications may become an obstacle to cancer treatments. Although comprehensive oral management, including oral care, the removal of dental focal infections, and improvements in oral function with dentures, is conducted for cancer patients in Japan, few studies have assessed its efficacy. The aim of the present study was to investigate the incidence of dental/oral complications in cancer patients with perioperative oral managements (POMs) based on a large number of case series with a multicenter retrospective analysis. The medical records of cancer patients with POMs were retrospectively reviewed and the incidence of oral complications and efficacy of oral management were investigated. A total of 2744 cancer patients with POMs (1684 males and 1080 females, mean age 65.9 ± 13.0 years) were included and investigated in the present study. Among these patients, 2097 (76.4%) started POM before the initiation of cancer treatments, with 2130 (77.6%) receiving oral care only and 391 (14.2%) being subjected to invasive treatments, such as tooth extraction. The incidence of dental focal infections during the period of cancer treatments was 8.2%. The most frequent infection was acute periodontitis, including alveolar abscesses (112 patients, 4.1%). The incidence of grade 2 and 3 oral mucositis was 2.8%. Prolonged fever was observed in 113 patients (4.1%), with 7 having dental focal infections (6.2%). These incidence rates were lower than those reported previously. Based on analyses of a large number of patients, the present results support the efficacy of oral management in cancer patients. However, further studies are needed to establish adequate oral management guidelines for cancer patients. Abstract : Supplemental Digital Content is available in the text